Pneumonia necrotizante por Staphylococcus aureus resistente à meticilina Necrotizing pneumonia due to methicillin-resistant Staphylococcus aureus - Pedro Alves d'Azevedo; Fernanda Matsiko Inoue; Soraya Sgambatti Andrade; Regina Tranchesi; Antonio Carlos Campos Pignatari (Revista da Sociedade Brasileira de Medicina Tropical, 2009)
O objetivo desse estudo foi descrever um caso de pneumonia necrotizante por Staphylococcus aureus resistente a meticilina. A amostra foi isolada em hemocultura coletada menos de 48 horas da admissão hospitalar. A paciente era previamente hígida quando do início do processo infeccioso. O isolado possuía o gene mecA, com "staphylococcal cassette chromosome mec" tipo IVa". A presença de Staphylococcus aureus carreando esse determinante genético em nosso meio deve ser considerada em pneumonias comunitárias graves. The aim of this study was to describe a case of necrotizing pneumonia caused by methicillin-resistant Staphylococcus aureus. The sample was isolated from a blood culture collected less than 48 hours after hospital admission. The patient had been healthy until the infectious process started. The isolate had the mecA gene with "staphylococcal cassette chromosome mec" (SCCmec) type IVa. The possibility that Staphylococcus aureus harboring this genetic determinant might be present in our setting should be considered in situations of severe pneumonia within the community.